Functional magnetic resonance imaging of reorganization in rat brain after stroke - Dijkhuizen, Rick M. (The National Academy of Sciences, 2001)
Functional recovery after stroke has been associated with brain plasticity; however, the exact relationship is unknown. We performed behavioral tests, functional MRI, and histology in a rat stroke model to assess the correlation between temporal changes in sensorimotor function, brain activation patterns, cerebral ischemic damage, and cerebrovascular reactivity. Unilateral stroke induced a large ipsilateral infarct and acute dysfunction of the contralateral forelimb, which significantly recovered at later stages. Forelimb impairment was accompanied by loss of stimulus-induced activation in the ipsilesional sensorimotor cortex; however, local tissue and perfusion were only moderately affected and cerebrovascular reactivity was preserved in this area. At 3 days after stroke, extensive activation-induced responses were detected in the contralesional hemisphere. After 14 days, we found reduced involvement of the contralesional hemisphere, and significant responses in the infarction periphery. Our data suggest that limb dysfunction is related to loss of brain activation in the ipsilesional sensorimotor cortex and that restoration of function is associated with biphasic recruitment of peri- and contralesional functional fields in the brain.